Rancang Bangun Aplikasi Perencanaan Pembelian Tepung Berdasarkan Peramalan Harga - Muchamad Alip Romdhoni; Sulistiowati Sulistiowati; Julianto Lemantara (Jurnal Sistem Informasi Universitas Dinamika, 2016)
Abstract: UD. Rohmat Jaya is a company engaged in the production of crackers. The raw materials used in the production of this company is tapioca starch. In the process of procurement of raw material powder, the company can not determine the price of flour in the next period. This resulted in companies often buy flour in large quantities at a time when prices are rising flour. The design of applications based on the purchase price forecasting flour takes part in company operations UD. Rohmat Jaya to predict the needs and flour prices next period and determine the allocation of the amount of purchase. With the application of the purchase price of flour based forecasting, operational sections can estimate the price of flour in the next month, using the Triple Exponential Smoothing (Winter) by calculating the price history of each flour to be predicted. Once tested , flour based planning application purchase price forecasting can predict the price and needs tapioca flour with Triple Exponential Smoothing method at UD . Rohmat Jaya and Determine the allocation of the amount of starch needs in the future . Based on forecasting system test and evaluation period at 20 Red Bear flour application has an error value of 5 % error